An addition to the alien flora of Java: the first record of adventive Costus dubius (Costaceae) - Wendy Achmmad Mustaqim; Eka Setiawan (Jurnal Biologi Tropis, 2021)
More than 6000 plant species, native and introduced, have been recorded in Java that includes the Costaceae family. In the last few years, several additions of alien Costus species have been published from Java. In 2019, a set of specimens of wild Costus sp. was collected from Institut Pertanian Bogor, Bogor, West Java Indonesia. This species is not similar to any previously recorded wild Costus in Java. Therefore, this research aims to identify the collected specimen and provide a taxonomic account for the species. The morphological description was made from the living plant and the collected herbarium. The description was used to identify the species, supported by field notes and photographs. The result showed that the recently collected specimen belongs to Costus dubius. Before this finding, the plant was only known in cultivation in the Bogor Botanical Garden. Therefore, this finding represents the first record of the adventive population of C. dubius in Java and increases the number of wild Costus in Java into seven species. Further researches on Costus in Java are suggested such as the ecological impact due to the presence of several non-native species.